(3GdaQGFO hGdbdGFOs - (3GdQTjO GdhWhGW , eMeO Hf eMeO Hf YHO GdLdjd Hf YHO Gdedc GdYeQj GdHdNj, QTjO GdOjf CHh HcQ,J (B573 (3g` s
(3ChdgG (B:s
(3hbO LeYfG ef EfTGFfG aj gPG GdcJGH CdaGXkG hLjRI CLQjfGgG eLQi GdCeKGd s
(3BNQgG (B:s
(3Jcde QLd aj eLdS GHf YHGU aNdW, abGd GHf YHGS(B: (3HcdGe eKdc QRb GdUjQ GdeMHI s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B25 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B229s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B81 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1243s
Keywords: (3GdCOHs